Nghiên cứu tính toán nhiệt lò rang đậu phụng - Tran , Ngọc Hào (Journal of Technical Education Science, 2007)
At present, technological processing and preserving groundnuts are very various and abundant, it made many products those are enough demand for human in Viet Nam and export passing other countries in the world to have profit from that technological process- ing and preserving. And one of the most preeminent products of groundnuts that is roast in an oven. However, the method of research for calculating heat, designing and making oven roast groundnuts is very complicated question. In this page, we will introduce a method to design and make oven roast groundnuts to serve the technological processing and preserving groundnuts in Viet Nam